The epiphytic bryoflora of the Jbel Bouhalla (Rif, Morocco), including a new variety of moss, Orthotrichum speciosum var. brevisetum. - Draper, I.; Lara, F.; Albertos, B.; Garilleti, R.; Mazimpaka, V. (Journal of Bryology, 2003)
The epiphytic bryoflora of Jbel Bouhalla, a mountain sited in the Rif range (northern Morocco), is catalogued, resulting in a list of 48 taxa (45 mosses and 3 liverworts). One new variety, Orthotrichum speciosum var. brevisetum, is described, and some new records are reported: Orthotrichum shawii and O. pallens are new to northern Africa, while Habrodon perpusillus and O. speciosum var. speciosum are new to Morocco. [ABSTRACT FROM AUTHOR]
Keywords: Bryophyte flora; chorology; epiphytes; Morocco; northern Africa; Orthotrichum speciosum var. brevisetum; Rif